Relationship between Parenting Styles and Academic Performance among Adolescents in Selected Schools of Rupandehi - Lamichhane, Kavita; Kachapati, Anuja; Bhandari, Sharmila; Bhattarai, Sigma; Vaidya, Gemorina; Shrestha, Sangam; Rawal, Shristee (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Children spend most of the time at home and parent’s attitude, behaviours, life standards and communication with children has greater inﬂuence on child growth and development. Parenting styles are representation of how parents respond and demand to their children. The present study aimed to investigate the relationship between the parenting styles and academic performance among adolescents. MATERIAL AND METHODS Cross-sectional study was conducted among 364 adolescents to ﬁnd out the relationship between parenting styles and academic performance at schools of Rupandehi by using non- probability convenience sampling technique. Socio-demographic data were collected using self-structured questionnaire. Parenting style was assessed by using Parental Authority Questionnaire and academic performance was measured by taking the average percentage obtained in the previous 3 annual examinations (7th, 8th and 9th standard). The data were analyzed by using descriptive and inferential statistics with Statistical Package for Social Sciences software version 20. RESULTS The results showed that 67.3% and 64.8% of the respondents reported that their mother and father adopted authoritative parenting style respectively. More than half (62.6%) of the respondents’ academic performance was good as they scored ﬁrst division in the previous annual examination. The results also showed that there is a weak positive correlation between mother and father authoritative parenting style with academic performance among adolescents. CONCLUSION Based on the ﬁndings, it is concluded that parenting style does not inﬂuence the academic performance among adolescents. Hence, there can be other contributing factors which may affect the academic performance among adolescents.